The level of acceptance towards Public Service Announcement (PSA) / Ummi Hazwani Abdullah ... [et al.] - Abdullah, Ummi Hazwani; Afandi, Maisarah Hanim; Mohd Nor, Nor Syamimi Nasuha; Mohamad Saad, Saidatun Nurasyiqin; Abdullah, Suhaizah; Saari, Izni Syamsina; Muhd Irpan, Hamidah (Faculty of Communication & Media Studies, 2022)
The Public Service Announcement (PSA) is an effective short message made via media that offered values, campaigns, programs, and community interests by providing information to the public. The footage consists of a powerful information to help viewers realize that this life is precious enough to be wasted. The aim of this study is to explore the acceptance towards PSA among Malaysians. There were 300 respondents of different demographic background was involved in this study using convenience sampling method. All of the data were used and analysed by using Statistical Package for the Social Science (SPSS) version 26.0. The findings have revealed that averagely respondents agreed that Public Service Announcement (PSA) can influence people thought (M=4.27), create awareness on the important message delivered (M=4.30) and leading to action taken by people as required by the message (M=4.19). PSA is proven to be accepted by respondents in this study (M=4.23)